Máscaras del desamor: nota a Palais de Justice (TEST Ticontre. Theory Text Translation, 2020)
This brief note aims to point out the relationship between subject and eroticism in Palais de Justice by José Ángel Valente (2014). Despite the closeness to the biographical fact, Valente does not renounce to explore the possibilities offered by the poetic word, which here faces a different and unexpected proof of its coherence. The subject questions his own identity while observing his own radical dissolution, at the same time as it tries to recover its own autonomy from to the other.